The Role of Physiotherapy in Improving Functional Capacity in Heart Failure- Research Oriented Trails (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Heart failure is a chronic clinical condition associated with reduced functional capacity and poor health-related quality of life. Exercise-based cardiac rehabilitation (ExCR), led by physiotherapy, has emerged as an effective non-pharmacological intervention for improving physical performance and overall well-being in this population. This research-oriented trial examines the impact of structured physiotherapy-based ExCR on functional capacity and quality of life in patients with heart failure. Using a positivist, deductive, experimental design, primary data are collected through questionnaires and analyzed using SPSS to evaluate changes in exercise tolerance and health-related quality of life. The study also explores the moderating effects of patient characteristics such as age, gender, NYHA functional class, left ventricular ejection fraction, and baseline exercise capacity. The findings aim to strengthen the evidence supporting physiotherapy-led cardiac rehabilitation and to inform more individualized, effective rehabilitation strategies for heart failure management.